Does Sleep Improve Memory Organization? - Takeuchi, Masashi; Furuta, Hisakazu; Sumiyoshi, Tomiki; Suzuki, Michio; Ochiai, Yoko; Hosokawa, Munehito; Matsui, Mie; Kurachi, Masayoshi (Frontiers in Behavioral Neuroscience, 2014)
Sleep can integrate information into existing memory networks, look for common patterns and distil overarching rules, or simply stabilize and strengthen the memory exactly as it was learned. Recent research has shown that sleep facilitates abstraction of gist information as well as integration across multiple memories, insight into hidden solutions, and even the ability to make creative connections between distantly related ideas and concepts. To investigate the effect of sleep on memory organization, 35 normal volunteers were randomly assigned either to the sleep (n = 17) or wake group (n = 18). The sleep subjects performed the Japanese Verbal Learning Test (JVLT), a measure of learning and memory, three times in the evening, and slept. On the following morning (9 h later), they were asked to recall the words on the list. The wake subjects took the same test in the morning, and were asked to recall the words in the same time interval as in the sleep group. The semantic clustering ratio (SCR), divided by the total number of words recalled, was used as an index of memory organization. Our main interest was whether the sleep subjects elicit a greater increase in this measure from the third to the fourth assessments. Time × Group interaction effect on SCR was not significant between the sleep group and wake group as a whole. Meanwhile, the change in the SCR between the third and fourth trials was negatively correlated with duration of nocturnal waking in the sleep group, but not other sleep indices. Based on this observation, further analysis was conducted for subjects in the sleep group who awoke nocturnally for <60 min for comparison with the wake group. A significant Time × Group interaction was noted; these “good-sleepers” showed a significantly greater improvement in the memory index compared with the wake subjects. These results provide the first suggestion that sleep may enhance memory organization, which requires further study.